Kompetensi, Karakter Individu, Etos Kerja dan Komunikasi terhadap Efektivitas Kerja Melalui Iklim Organisasi Pada Masa Pandemi Covid-19 - Anik Yuanawati; Eka Askafi (Otonomi, 2022)
One of the roles of human resources is reflected in the duties of the government apparatus (ASN) in various aspects in this pandemic era becoming more complex due to the demands of changing times and new work patterns. The purpose of this study was to analyze competence, individual character, work ethic and communication on work effectiveness through the organizational climate during the covid-19 pandemic. This research is a quantitative research in the form of explanatory research with causality. The population of this research is the entire apparatus of the General Section of Blitar Regency, totaling 37 employees. Sampling in this study was carried out with saturated samples or called total sampling. The analytical tool used in this study is path analysis which is assisted by using the SPSS version 20 program. The results of the research carried out are related to competence, individual character, work ethic and communication on work effectiveness through the organizational climate during the covid-19 pandemic, it can be concluded that there are 2 The hypothesis that has no effect is work ethic on work effectiveness through organizational climate and work ethic on work effectiveness variables.